Long-term safety and efficacy of deferasirox in patients with myelodysplastic syndrome, aplastic anemia and other rare anemia in Taiwan. Issue 1 (1st January 2019) - Ko, Bor-Sheng; Chang, Ming-Chih; Chiou, Tzeon-Jye; Chang, Te-Kau; Chen, Yeu-Chin; Lin, Sheng-Fung; Chang, Cheng-Shyong; Lu, Yin-Che; Yeh, Su-Peng; Chen, Tsai-Yun; Hwang, Wei-Shou
ABSTRACT: Objective: Patients with myelodysplastic syndromes (MDS), aplastic anemia (AA) or other rare anemia require chronic blood transfusions which can lead to iron overload and subsequent excess iron-mediated complications. Intensive iron chelation with deferasirox could remove excess iron and can alleviate these events; however, the long-term safety and efficacy in Chinese population are not clearly characterized. This study examined the long-term efficacy and safety of deferasirox in a real-world setting in Taiwan. Methods: This observational, non-interventional, single-arm, multi-center, phase IV study was designed to collect the safety and clinical information about patients who were treated with deferasirox according to investigator's judgment and in accordance with the general clinical practice. Results: From 2009 to 2011, patients with MDS ( N = 38), AA ( N = 23), and other rare anemias ( N = 18) were enrolled. The mean deferasirox exposure was 17.7 ± 4.02 mg/kg/day. The most common drug-related AEs were skin disorders (32.9%) and gastrointestinal disorders (30.4%), while grade 3–4 AEs were rare (5.1%). In the overall patient population, deferasirox effectively decreased serum ferritin levels at 1 year ( P = 0.0154) and 3 years ( P = 0.0424) from the baseline. Upon the use of deferasirox, 32.9% patients showed erythroid response and 16.7% patients had platelet response. Conclusions: For patients with MDS, AA, and other rare anemias, the AEs observed in this 3-year surveillance study with deferasirox were mostly mild or moderate. In addition, the hematological response rate was higher than that in the EPIC study, which primarily enrolled Caucasian patients.